Pelatihan dan Pengembangan Usaha Ekonomi Mikro di Desa Karangdiyeng Kecamatan Kutorejo Kabupaten Mojokerto - Nugroho, Tatas Ridho; Ainiyah, Nur; Nirmala, Dindya (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of science and technology brings people to the level of the industrial revolution called the Revolution 4.0. Revolution 4.0 makes things easier with the internet. The use of the internet is driving the growth of new economic resources known as digital economies, describing how the internet is changing the way people do business. The Digital Economy is used by UMKM to compete and develop in international economic trade, hoping to increase revenue. Thus, in an increasingly digital economy, internet-based UMKM business activities need to be carried out. Following up on this, on November 8, 2017, it was announced that UMKM Go Online was one of the efforts to lift UMKM by utilizing internet technology. One effort is to provide training so that UMKM can expand their business through the internet, or what is known as UMKM Go Online.